Socio-Economic Impact of Telework for Workers with Disabilities in Indonesia - Darin Atiandina; Shanti Darmastuti (Jurnal Studi Sosial dan Politik, 2023)
The COVID-19 pandemic has changed the structure of people's lives, including the work models. The telework work model is increasingly being used because it is considered capable of facilitating mobility, cost efficiency, and offering time flexibility for workers. Most studies about telework and disabled persons focus on cases in developed countries and increasing job opportunities. This study aims to provide an overview of the socio-economic impact of telework on Persons with Disability (PwD) in developing countries, specifically in Indonesia. This study uses a qualitative method with case study approach. Data were collected by in-depth interviews and literature studies on articles, journals, books, and open-source references regarding telework and disability. This study found that the telework model has made disabled workers in Indonesia even more marginalized. Moreover, the telework model had triggered financial difficulties among disabled workers, such as salary cuts, temporary and permanent lay-offs, and job loss. Furthermore, this is because most disabled workers in Indonesia have low education level, skills, limited access to the internet, and limited access to telework facilities. Meanwhile, this study aims to provide an overview of socio-economic impact from telework models on disabled persons in developing countries, especially in Indonesia, where most disabled persons have low education level and poor digital skill. This study offers recommendations to create an inclusive telework market, that is; conduct job analysis, improve the education system and digital skill for PwD, provide assisting and supporting facilities, guarantee for workers with disability, as well as monitoring and evaluation.